PENGARUH KINERJA KEUANGAN TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY PADA PERUSAHAAN MANUFAKTUR - Rochmawati, Ika; Kurnia, Kurnia (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
This research is meant to examine the influence of financial performance to the disclosure of Corporate Social Responsibility (CSR). The disclosure of Corporate Social Responsibility (CSR) has an important role in the company to maintain the relation, and it is also the long term investment for the business continuity. The result of analysis shows that the financial performance which is measured by Return on Assets (ROA) and Return on Equity (ROE) do not have any significant influence to the Corporate Social Responsibility (CSR), meanwhile the financial performance which is measured by using Net Profit Margin (NPM) has significant influence to the Corporate Social Responsibility (CSR).Keywords: Return on Assets (ROA), Return on Equity (ROE), Net Profit Margin (NPM), Corporate Social Responsibility (CSR).